Pemanfaatan Paitan (Tithonia diversifolia) sebagai Pupuk Organik pada Tanaman Kedelai - Sri Ayu Dwi Lestari (Iptek Tanaman Pangan, 2016)
Paitan is an annual weed which can be used as organic manure for crops. The yield of biomass is about 9-11 t/ha during the dry season and 14-18 t/ha during the rainy season. As a source of N, P, K nutrients for plants, paitan contains 3.50-4.00% N, 0.35-0.38% P, 3.50-4.10% K, 0.59% Ca, and 0.27% Mg. Biomass of paitan can be used as a green manure, mulch, or compost to improve physical and biological soil fertility. The leaves and stems used as organic manure can improve the growth and yield of soybean. Application of paitan biomass before the seed planted, however, may suppress the growth of soybean seed due to its alelopatic effect to seedling. Therefore, application of fresh paitan biomass is suggested after the seeds germinate, at 3-4 weeks after planting.